Performance Evaluation of Raw Material Suppliers at Manufacturing Company Using Analytical Hierarchy Process Method - Rio Febryan; Resista Vikaliana (School of Industrial and System Engineering, Telkom University, 2023)
PT Trafoindo Prima Perkasa is a medium-sized electrical equipment manufacturing company that usesbushings as raw materials for transformers. Therefore, it is important to evaluate bushing suppliers toensure the appropriate quality and quantity of raw materials. Currently, the company faces issues withdelayed raw material deliveries, which disrupt production. The research aims to evaluate the performanceof bushing raw material suppliers using the Analytical Hierarchy Process (AHP) method, focusing onprice, quality, service, and delivery. The AHP method is employed for multi-criteria decision-making insupplier performance evaluation through questionnaires and analysis using Expert Choice software. Theanalysis results indicate that price is the primary evaluation criterion with a value of 0.398, and Supplier Ademonstrates the best performance with a score of 0.280.